Effects of TiO2 additive on ultra-low-loss MgO–LiF microwave dielectric ceramics. Issue 5 (1st April 2020) - Tan, Zhenyu; Lin, Huixing; Song, Kaixin; Dang, Mingzhao; Yao, Xiaogang; Ren, Haishen; Xie, Tianyi; Peng, Haiyi
Abstract: MgO ceramics have good microwave dielectric properties, but the high sintering temperatures limit its application. The effects of TiO2 additive on the phase composition and microwave dielectric properties of MgO ceramics with 4mol%LiF were investigated by solid state reaction method. TiO2 and MgO form Mg2 TiO4 in a magnesium-rich environment with 4mol%LiF at about 900 °C, which as a solid solution or second phase had a huge impact on MgO ceramic with 4mol % LiF. When the content of TiO2 less than 2mol %, Mg2 TiO4 as a solid solution in MgO ceramics, which made the grain of MgO larger. When the content of TiO2 more than 2mol %, Mg2 TiO4 as a second phase in MgO ceramics, which made the microwave dielectric properties of MgO ceramics bad. Typically, the MgO-4mol%LiF-0.5mol%TiO2 ceramic sintered at 1075 °C for 6 h acquired the best dielectric properties: εr = 9.7, Qf = 617, 000 GHz and τf = −59.49 ppm/°C.